Representasi Konten Humor dalam Iklan Televisi Shampo Head & Shoulders - Putra Akbar Pradina; Raditya Pratama Putra (Bandung Conference Series: Communication Management, 2023)
Abstract. Humor is an attitude that tends to be done to evoke joy and trigger laughter. We can find humor on any platform, for example on television shows and advertisements. There are lots of advertisements that use elements of humor in it to attract people's attention. Indirectly advertisements that use elements of humor to make people who watch are interested. In this study the method used was qualitative method using interview techniques and direct field observation in order to obtain the necessary data with the Ferdinand De Saussure Semiotic Analysis approach in perfecting this research report. This study aims to determine the meaning of Significe (marker) contained in head & shoulder shampoo advertisements. This is to find out the meaning of Signified (signified) and the advertising ethics contained in Head & Shoulder shampoo advertisements. There are as many as 29 million viewers who watch YouTube Head & Shoulders ads. Therefore, researchers are very interested in finding more in-depth information about Joe Taslim Head & Shoulders humorous Youtube advertisements. Based on the formulation of the problem and the results of the research, it can be concluded that there are signifiers, signifiers, and humor ethics in the research entitled "Representation of Humor Content in Head & Shoulders Shampoo Television Advertisements". and mistakes, the achievement of perfect results requires a solid team and does not give up under any circumstances is the meaning of the sign, humorous scenes that are studied using existing theories give birth to value. Abstrak. Humor merupakan sikap yang cenderung dilakukan untuk membangkitkan rasa gembira dan memicu gelak tawa. Humor dapat kita temukan pada platform apapun, contohnya pada acara televisi dan iklan. Terdapat banyak sekali iklan yang menggunakan unsur humor didalamnya untuk menarik perhatian masyarakat. Secara tidak langsung iklan yang menggunakan unsur humor guna membuat masyarakat yang menonton tertarik. Dalam penelitian ini metode yang digunakan adalah metode kualitatif dengan menggunakan teknik wawancara dan observasi langsung ke lapangan guna memperoleh data yang diperlukan dengan pendekatan Analisis Semiotika Ferdinand De Saussure dalam menyempurnakan laporan penelitian ini. Penelitian ini bertujuan untuk mengetahui makna Signifie (penanda) yang terdapat pada iklan sampo head & shoulder. Hal ini guna mengetahui makna Signified (petanda) serta etika periklanan yang terdapat pada iklan sampo Head & Shoulder. Terhitung sebanyak 29 juta penonton yang menonton iklan Youtube Head & Shoulders. Oleh karena itu, peneliti sangat tertarik mencari informasi lebih dalam tentang iklan Youtube humor Joe Taslim Head & Shoulders. Berdasarkan dari rumusan masalah dan hasil penelitian maka dapat ditarik kesimpulan bahwa terdapat makna petanda, penanda, dan etika humor terhadap penelitian yang berjudul “Representasi Konten Humor Dalam Iklan Televisi Shampo Head & Shoulders” Terdapat dua makna mengenai penanda yaitu dalam bekerja pasti terdapat begitu banyak rintangan dan kesalahan, tercapainya kesempurnaan hasil dibutuhkan tim yang solid dan tidak pantang menyerah dalam keadaan apapun merupakan makna penanda, Adegan-adegan humor yang dikaji menggunakan teori-teori yang ada melahirkan nilai.